2014
DOI: 10.1093/bja/aeu292
|View full text |Cite
|
Sign up to set email alerts
|

The State of UK anaesthesia: a survey of National Health Service activity in 2013

Abstract: Anaesthesia in the UK is currently predominantly a consultant-delivered service. The low mortality rate supports the safety of UK anaesthetic care. The survey data should be valuable for planning and monitoring anaesthesia services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
141
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(142 citation statements)
references
References 11 publications
0
141
0
1
Order By: Relevance
“…For the analysis of risk factors, we compared the relative frequencies of features in AAGA reports with the frequency of those in the NAP5 activity survey [5].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the analysis of risk factors, we compared the relative frequencies of features in AAGA reports with the frequency of those in the NAP5 activity survey [5].…”
Section: Methodsmentioning
confidence: 99%
“…Two of its stated aims included estimating an incidence of reports of AAGA and determining risk factors. The methodology is described in an accompanying paper [4] and together with its activity survey [5], makes NAP5 the largest and most comprehensive study on AAGA and its risk factors ever undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…Overviews of the project have been described in part elsewhere [23][24][25][26][27][28]. The NAP5 project was approved by the National Information Governance Board in England and Wales, and Patient Advisory Groups in Scotland and Northern Ireland.…”
Section: Methodsmentioning
confidence: 99%
“…The UK and Irish baseline [24,26] and activity [27,28] surveys have been published in full and details will not be repeated here.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, the denominator (total number of general anaesthetics) is unclear from the NAP5 results. It is indirectly inferred (with an undisclosed percentage error) from the activity surveys [6,7], and is further complicated by the fact that almost a quarter of the cases (35/141) actually occurred before the study commenced, but had not been previously reported to a health professional. In essence, the investigators were sampling from the population of all general anaesthesia survivors from 1946 to the present, who had not previously reported any intra-operative recall, and who had also chanced to be exposed to the investigation team.…”
Section: Essential Findingsmentioning
confidence: 99%